ASPEK-ASPEK KOMUNIKASI DALAM PROSES KEKARYAAN SENI PERTUNJUKAN - Widodo, Anhar (Institut Seni Indoensia Surakarta, 2009)
This research try to expose all the kind of human communications in pe,formance artâ€”especially dance. Indeed, human communication is usefulifor creative process of idea exploration. With qualitative approach and interview method to digg various data, this research expose a kind of communication context that built in creative pmcess of dance arts. The Director of one of a masterpiece peiformance art, Kalabendu, HDwi Wahyudiarto, S. Kar, M. Hum. will be the main source.Balancing interaction and adaptation that match with each portion dan responsibility, make creative performance art process so smooth to be done. A democratic culture, full filling in purpose to reach the best, will guarantee a creative independence an searching creativity exploration to gain the beginning aimâ€”that match with the deal in the first outline scenario. Various communication define of seven specific contextual circumstances. That was two persons communication; interview; a little communication group; public communication; organizational communication; mass communication; and inter-cultural communication. Shape of communication that built in art making process more intens to balancing reciprocal communication. Group and personal communication together in linear concept between communicator and communican in gainning the same purpose.Â Key words: communication contexts, art, democratic, kalabendu.